linear equations

Asked by devanshmudgal | 28th May, 2010, 07:31: PM

Expert Answer:

Dear Student,

x+y=a+b...........................(1)

And

ax-by=a2-b2 .......................(2)

On multiplying eqn (1) by 'b', we get,

bx+by=ab+b2 .....................(3)

On adding eqn(2) and (3), we get,

(a+b)x = a2-b2 + ab +b2

=>(a+b)x =a(a+b)

=> x=a

Substitute this value of x in eqn(1)

So, a+y=a+b

=> y=b

Regards Topperlearning.

 

Answered by  | 29th May, 2010, 11:28: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.